2019
DOI: 10.1213/ane.0000000000004066
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cognitive and Functional Impairments After Critical Illness

Abstract: As critical illness survivorship increases, patients and health care providers are faced with management of long-term sequelae including cognitive and functional impairment. Longitudinal studies have demonstrated impairments persisting at least 1–5 years after hospitalization for critical illness. Cognitive domains impacted include memory, attention, and processing speed. Functional impairments include physical weakness, reduced endurance, and dependence on others for basic tasks of daily living such as bathin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 73 publications
4
90
1
4
Order By: Relevance
“…This observation is important as the prevalence of cognitive impairment increases with age. In a recent review Rengel and colleagues 14 reported that baseline cognitive impairment is a risk factor for cognitive impairment following critical illness. To account for the possibility that cognitive impairment at SV1 may simply reflect a higher prevalence of a premorbid state, patients were stratified by the IQCODE 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This observation is important as the prevalence of cognitive impairment increases with age. In a recent review Rengel and colleagues 14 reported that baseline cognitive impairment is a risk factor for cognitive impairment following critical illness. To account for the possibility that cognitive impairment at SV1 may simply reflect a higher prevalence of a premorbid state, patients were stratified by the IQCODE 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients surviving critical illness generally risk long-term cognitive impairment and reduced health-related quality of life (HRQoL). [1][2][3][4][5][6][7] Some survivors even report their health to be unacceptable. 8 The prevalence of cognitive impairment varies widely across studies, but 1 review estimated a prevalence of persistent cognitive impairment of 20%-40% of intensive care unit (ICU) survivors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in critical care, COVID-19 patients present with Acute Respiratory Distress Syndrome, for which the medical management, role of physiotherapy, rehabilitation interventions and outcome measures are well known. [3][4][5][6][7][8] We need not start from scratch preparing lists of what physiotherapists need to know to redeploy to the intensive care unit. Minimum standards of clinical practice for physiotherapists in critical care in Australia and New Zealand 9 and in the United Kingdom 10 have already been established, and should be used to guide training and upskilling.…”
mentioning
confidence: 99%